INVESTOR PERLU MENGINDENTIFIKASI INDEKS SAHAM USA UNTUK MEMPREDIKSI FLUKTUASI IHSG: LINCOM ANALYSIS - Widianto, Tri; Khristiana, Yenni; Murti, Nugroho Wisnu (Jurnal Analisis Bisnis Ekonomi, 2018)
First objective of this study is to identify the influence of the fluctuations in the entire United States stock index on the Indonesian Composite stock Index. The results of thisstudy be used to predict Indonesian Composite indexes in a certain period of timebase of USA indexes fluctuation. The second objective is to find out whether there was a significant difference between the influence of the United States stock indexes on the Indonesian composite index. We used time series secondary data of daily stock price index over in five years (January 1, 2013 to December 31, 2017). The sample selection method used non-probability sampling with purposive sampling technique. We used robust simple regressionto achieve the first goal is, while the second goal used the linear combination. The results analysis showed that all of types of United States stock indices are partially significant and positive to Indonesian Composite index fluctuations (P-Value <0.05). Several types of USA stock indices have a significantly different coefficient in influencing Indonesia's Composite index between the Dow Jones Composite and the NYSE Composite and Dow Jones Composite with OTCM ADR (P-Value <0.05). Thus, the results of this study provide advice to investors, especially the Swinger and Scalper types, that considering the fluctuations in the USA index as a stock investment decision in Indonesia, it does not only consider one type of index, which is currently the headline of the stock index in the USA for example (Dowjones 30). However, consider other indices both composite and specific composite.